1995
DOI: 10.1111/j.1475-6811.1995.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving in the close relationships of cardiac patients: Exchange, power, and attributional perspectives on caregiver resentment

Abstract: Individuals with a cardiac condition and their spousal caregivers were recruited from cardiac rehabilitation centers and interviewed separately. Based on exchange theory, it was expected that greater caregiver resentment would be associated with feeling underbenefited in the relationship and with an orientation to relationships that did not focus on the needs of the partner (communal), but did focus on “tit‐for‐tat” reciprocity (exchange). It was also expected that those caregivers who were more likely to get … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…The underbenefited partner is likely to feel less committed or attached to the relationship and also to experience anger toward the partner. Previous research on cardiac patients and their family member caregivers found that the caregivers who felt they were underbenefited were more resentful of their partner (Thompson, et al, 1995). The purpose of this part of the study was to replicate the Thompson et al (1995) finding with a sample of stroke patients and caregivers and then to examine the relationship between caregivers' perceptions of underbenefit and feelings of overprotection on the part of patients.…”
Section: Exchange Theory: Resentment and Overprotectionmentioning
confidence: 86%
See 3 more Smart Citations
“…The underbenefited partner is likely to feel less committed or attached to the relationship and also to experience anger toward the partner. Previous research on cardiac patients and their family member caregivers found that the caregivers who felt they were underbenefited were more resentful of their partner (Thompson, et al, 1995). The purpose of this part of the study was to replicate the Thompson et al (1995) finding with a sample of stroke patients and caregivers and then to examine the relationship between caregivers' perceptions of underbenefit and feelings of overprotection on the part of patients.…”
Section: Exchange Theory: Resentment and Overprotectionmentioning
confidence: 86%
“…Previous research on cardiac patients and their family member caregivers found that the caregivers who felt they were underbenefited were more resentful of their partner (Thompson, et al, 1995). The purpose of this part of the study was to replicate the Thompson et al (1995) finding with a sample of stroke patients and caregivers and then to examine the relationship between caregivers' perceptions of underbenefit and feelings of overprotection on the part of patients. If support is found for the Resentment Model as a source of patient overprotection, then it follows that caregiver perceptions of inequity may be associated with overprotective care, as felt by the patient.…”
Section: Exchange Theory: Resentment and Overprotectionmentioning
confidence: 86%
See 2 more Smart Citations
“…Buunk and Schaufeli (1999) took an evolutionary approach to reciprocity, suggesting that it is a basic psychological mechanism that developed to maintain social relationships and indicate individuals' importance in their social groups. Research on couples in which one member is seriously ill has shown that both the ill spouse and the caregiving spouse suffer from frustration, anger, depression, and resentment when the relationship is not judged to be reciprocal (Thompson, Medvene, & Freedman, 1995).…”
Section: Support Receipt and Increased Distressmentioning
confidence: 99%